Physiological quality and germination energy of bitter gourd (Momordica charantia L.) seeds - Barraza A., Fernando; Benavides B., Orlando; Torres M., Francisco (Revista de Ciencias Agrícolas, 2016)
Bitter gourd seeds present germination difficulties due to the thick and hard seed coat that surrounds the embryo. The objective of this study was to evaluate the effect of bitter gourd seed imbibition on germination energy, absolute rate of germination, and germination index. A completely randomized experimental design with three treatments was used: T0 (control, without imbibition), T1 (seed imbibition at 22°C during 24 hours), and T2 (seed imbibition at 50°C during 60 minutes). Treatment T1 is recommended over the other treatments, because it improved germination energy (48%), absolute rate of germination (8.6 seeds∙day-1), and germination index (11.5).